PERLAKSANAAN SIYASAH SYAR'˜IYYAH DALAM PENTADBIRAN DI MALAYSIA - Che Pa, Bharudin; Basir, Siti Arni; Mohamed, Shukeri (Journal of Al-Tamaddun, 2010)
Siyasah Syar'iyyah deals with state administration and affairs which is in accordance with syariah rules. The coverage of Siyasah Syar'iyyah is huge that encompasses politics, administration, financial, economy and social affairs. The ultimate aim of Siyasah Syar'iyyah execution is to assure public interest and benefits. This paper discusses Siyasah Syar'iyyah practices within the context of administration in Malaysia. There are four administration programmes that are discussed i.e. Islamic Values Installation Policy, Halal Hub Program, Social Responsibility and the establishment of Malaysian Standard (MS) 1900: 2005 from Islamic Perspective.